2007
DOI: 10.1007/s10823-006-9028-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Affect Older Japanese People’s Reluctance to Use Home Help Care and Adult Day Care Services

Abstract: The purpose of this study was to examine the factors related to the reluctance of older Japanese people to utilize home help services and day services. Home help services consist of three different types of services (i.e., assisting in bathing and toileting, doing household choirs, such as cooking and laundry, and counseling) and are provided by visiting home helpers at the homes of older people. Day services are services (e.g., providing bathing and meals, monitoring the health status of older people, and cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…A recent study showed that the average entitlement rate rose from 13% in 2001 to 17.4% by 2006 (Mitchell, Piggott, and Shimizutani 2006). Despite initial reluctance to utilize care services when the program was first implemented (Tsukada and Saito 2006), utilization rates, particularly in the home health care area, have increased over the years (Mitchell, Piggott, and Shimizutani 2006).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…A recent study showed that the average entitlement rate rose from 13% in 2001 to 17.4% by 2006 (Mitchell, Piggott, and Shimizutani 2006). Despite initial reluctance to utilize care services when the program was first implemented (Tsukada and Saito 2006), utilization rates, particularly in the home health care area, have increased over the years (Mitchell, Piggott, and Shimizutani 2006).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…If this is one of the reasons, then information, exposure, and experience with this type of service may encourage many more to use it. For example, in Japan (Tsukada & Saito, 2006) older people who did not experience formal homecare and day care center services were reluctant to use them, but after experiencing these two types of services, they had a lower probability of feeling reluctant about using them. However, because the present study did not examine the reasons for nonuse of this type of service this issue merits further in-depth scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…2001; Walters, Iliffe, and Orrell 2001). On the other side, being familiar with care options increased the probability of using them (Cho 2005) and could help to overcome a possible reluctance to do so (Tsukada and Saito 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in countries which provide a welfare system showed that people with low income were more inclined to use home care (van der Heyden et al. 2003) or day services (Tsukada and Saito 2006). Economic obstacles depend thus on the perceived relation between income and cost of services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation